Distribution Model of Particulate Dust From Chimney of Sidoarjo Sugar Factory - S. Syahrorini; Arief Rachmansyah; Soemarno Soemarno; S. H. Pramono (Graduate Program, 2018)
Sugar factories in Indonesia are mostly built during the colonial era and therefore are not equipped with suitable environmental management equipment One of the effects of this activity is air pollution in the form of particulate matter from bagasse burning for energy. This study aims to determine the particle distribution of sterile emissions from the Sidoarjo Sugar Factory. The measurement of the sampling point with degradable dust collectors SNI 13-4703-1998 has been revised. The measuring point is scattered around the location of the sugar mill with a certain distance from the center of the chimney. The measurements are carried out for 24 hours at six-hour intervals so that the measurements at each sampling point are four times as long. The results of the particle dust measurements were analyzed by gravimetric method to obtain the particle dust concentration. Computer simulations are presented in the form of contour maps and 3D surface contours from particle dust concentrations. The simulation results show differences in the contour pattern and 3D surface contour due to differences in particle concentration for each measurement period. Each measurement period is also affected by wind speed and direction as well as measuring time by day or night.Keywords: Contour, Dust Faal Collector, Distribution Model, Particulate, Surface